If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 30 = 12x + -15 Reorder the terms: 30 + 4x = 12x + -15 Reorder the terms: 30 + 4x = -15 + 12x Solving 30 + 4x = -15 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 30 + 4x + -12x = -15 + 12x + -12x Combine like terms: 4x + -12x = -8x 30 + -8x = -15 + 12x + -12x Combine like terms: 12x + -12x = 0 30 + -8x = -15 + 0 30 + -8x = -15 Add '-30' to each side of the equation. 30 + -30 + -8x = -15 + -30 Combine like terms: 30 + -30 = 0 0 + -8x = -15 + -30 -8x = -15 + -30 Combine like terms: -15 + -30 = -45 -8x = -45 Divide each side by '-8'. x = 5.625 Simplifying x = 5.625
| 13-9x=198-44x | | 4k^2-9k-5=0 | | 2(4x-1)=22 | | 11x-31=7x+4 | | y-1/y-3=(y-1/y+5)+1 | | 17/3x+3/5=8/3x | | X^1/3-2=0 | | 2x^4-2=160 | | 6x-13=3(2x+9) | | y=-4/x+3 | | 8t-26=-30 | | 21/25=x/75 | | 7y=2+5x | | 2v+26=6v+30 | | 4(3y-2)+2(3y-2)= | | (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= | | (2x)-(x-4)=5 | | f-(4/1/3)=10 | | 4x+8(x+1)+4=12-4x |